2011
DOI: 10.1371/journal.pone.0014769
|View full text |Cite
|
Sign up to set email alerts
|

Molar Macrowear Reveals Neanderthal Eco-Geographic Dietary Variation

Abstract: Neanderthal diets are reported to be based mainly on the consumption of large and medium sized herbivores, while the exploitation of other food types including plants has also been demonstrated. Though some studies conclude that early Homo sapiens were active hunters, the analyses of faunal assemblages, stone tool technologies and stable isotopic studies indicate that they exploited broader dietary resources than Neanderthals. Whereas previous studies assume taxon-specific dietary specializations, we suggest h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(124 citation statements)
references
References 64 publications
4
117
2
1
Order By: Relevance
“…Studies of modern foragers document a cline in plant food consumption, with groups living in tropical latitudes consuming more plant foods than those in temperate or arctic latitudes (Kelly, 1995). Studies of Neanderthal dietary behavior have also suggested that ecogeographic factors influence dental microwear and mesowear (El Zaatari et al, 2011;Fiorenza et al, 2011). We predict that the geographic region from which samples came should also influence plant food consumption.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Studies of modern foragers document a cline in plant food consumption, with groups living in tropical latitudes consuming more plant foods than those in temperate or arctic latitudes (Kelly, 1995). Studies of Neanderthal dietary behavior have also suggested that ecogeographic factors influence dental microwear and mesowear (El Zaatari et al, 2011;Fiorenza et al, 2011). We predict that the geographic region from which samples came should also influence plant food consumption.…”
Section: Introductionmentioning
confidence: 79%
“…First, detailed analyses of both Neanderthal dental microwear (El Zaatari et al, 2011) and dental mesowear (Fiorenza et al, 2011) have suggested more variation within Neanderthal diets than previously expected. In both cases, Neanderthal groups living in southern and wooded environments had dental wear more similar to that of modern forager groups that consume a variety of foods, while Neanderthals in more northern and dry environments had diets similar to modern forager groups that consume predominantly meat.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a wider perspective, it is believed that future experimental studies of occlusal movement, in combination with wear pattern analyses such as the OFA (Kullmer et al, 2009), will help to elucidate the correlation between food properties, occlusal movements, and tooth wear. The quantitative method applied here lends itself to analyses concerning the development of wear facets (Fiorenza et al, 2010(Fiorenza et al, , 2011a, the correlation between facet microstriations and macrowear dip directions, and to the interpretation of differences, variability, and creation of tooth wear patterns. As the macrowear pattern reflects a long chronologic record of occlusal movements and behavior, it is here emphasized the potential of such studies for the reconstruction of dietary variability, mastication behavior, and evolutionary adaptation in fossil (e.g., paleontologic and paleoanthropologic) and modern species.…”
Section: Discussionmentioning
confidence: 99%
“…A stereotypic motion of the lower jaw was described as a general feature of the primate masticatory cycle Kay, 1972, 1973;Kay and Hiiemae, 1974;Kay, 1977;Maier, 1977Maier, , 1978Maier, , 1984, from which a maximum of 13 complementary facet pairs develop on the molar occlusal surface (Maier and Schneck, 1981). Accordingly, even though several factors (i.e., food properties, environmental, and behavioral factors) influence the shape, size, and gross rate of facet wear (Janis, 1990;Lussi, 2008;Fiorenza et al, 2011a), their topographic position on the occlusal surface mainly depends on crown morphology, the relationship of antagonistic cusps and basins, and jaw movements (Fiorenza et al, 2010(Fiorenza et al, , 2011b. Based on this, Kullmer et al (2009) proposed that a detailed analysis of a wear facets spatial position (occlusal fingerprint analysis, OFA) could precisely predict individual occlusal jaw movements.…”
Section: Introductionmentioning
confidence: 99%